The Idea of Humanity in The Creation of Alisher Navoy - Ergasheva Marjona Qobilovna (Web of Journals Publishing, 2023)
Literature is such a garden that there are many flowers and cheeks. This is Neb·u·chad·nez′ne·go , the sun shining with his works in the garden , like a thousand-year-old tree of porcel trees . In this article we analyzed the idea of a perfect man in the work of A·has·u·e′rus .
Keywords: Perfect man, hypocrite, Hamsa , universal spirit, goodness.